Evolution of Regeneration in Animals: A Tangled Story - Elchaninov, Andrey; Sukhikh, Gennady; Fatkhudinov, Timur (Frontiers in Ecology and Evolution, 2021)
The Evolution of regenerative capacity in multicellular animals represents one of the most complex and intriguing problems in biology. How could such a seemingly advantageous trait as self-repair become consistently attenuated by the evolution? This review article examines the concept of the origin and nature of regeneration, its connection with the processes of embryonic development and asexual reproduction, as well as with the mechanisms of tissue homeostasis. The article presents a variety of classical and modern hypotheses explaining different trends in the evolution of regenerative capacity which is not always beneficial for the individual and notably for the species. Mechanistically, these trends are driven by the evolution of signaling pathways and progressive restriction of differentiation plasticity with concomitant advances in adaptive immunity. Examples of phylogenetically enhanced regenerative capacity are considered as well, with appropriate evolutionary reasoning for the enhancement and discussion of its molecular mechanisms.